(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article presents the results of scientific research conducted in 2023 to determine the differences in the average values of important agronomic traits of the new medium-fiber cotton variety “Kelajak-3”, developed by breeders of the Republic of Uzbekistan. The traits studied included 1000-seed weight, seed cotton weight per boll, fiber yield, and fiber length. These indicators were compared with the standard varieties Namangan-77 and S-6524. The results showed that under the soil and climatic conditions of the Tashkent region, the plants of this variety demonstrated positive differences in all analyzed traits compared to the standard varieties. Based on the obtained data, conclusions and recommendations were provided regarding the wide introduction of this genotype into agricultural production and its use in breeding programs.